Real-Time Tracking of Photoinduced Metal-Metal Bond Formation in a d8d8 Di-Iridium Complex by Vibrational Coherence and Femtosecond Stimulated Raman Spectroscopy - Kloz, Miroslav; Dostál, Jakub; Mukherjee, Atripan; Pižl, Martin; Šebesta, Filip; Hill, Michael G; Gray, Harry B; Záliš, Stanislav; Vlček, Antonín (Journal of the American Chemical Society, 2025)
We report real-time dynamics of photoinduced metal-metal bond formation acquired from ultrafast time-resolved stimulated emission and femtosecond stimulated Raman spectra (FSRS) of [Ir2(2,5-dimethyl-2,5-diisocyanohexane)4]2+ (Ir(TMB)) in the region of low-frequency vibrations. Interpretation was supported by impulsive stimulated Raman experiments and time-dependent density-functional theory (TDDFT) calculations. The Ir-Ir stretching frequency doubled on going from ground to the lowest singlet excited state 1dσ*pσ, from 53 to 126 cm-1, demonstrating Ir-Ir bond formation. Spectral evolution during the first 4 ps after excitation showed extremely large-amplitude coherent oscillations of stimulated emission as well as FSRS signal intensities, which occurred with the excited-state Ir-Ir stretching frequency combined with frequencies of several deformation vibrations and the first Ir-Ir overtone. Corresponding vibrations were observed in FSRS directly but most of them vanished in the first 3 ps, indicating that they belonged to transiently populated hot vibrational states. Fourier transforms of intensity oscillations plotted against FSRS frequencies produced two-dimensional (2D-FSRS) maps with diagonal and off-diagonal features due to Franck-Condon-excited and anharmonically coupled vibrations, some of which acquired Raman intensity through coupling with the Ir-Ir stretch. We concluded that optical excitation impulsively shortens the Ir-Ir distance and increases its stretching force constant, assisted by a simultaneously excited network of coupled deformation modes. The electronically/vibrationally excited system then relaxes through periodic strengthening and weakening of the Ir-Ir interaction and changing conformations of the TMB ligand framework, forming a metal-metal bonded 1dσ*pσ state after 4-5 ps.We report real-time dynamics of photoinduced metal-metal bond formation acquired from ultrafast time-resolved stimulated emission and femtosecond stimulated Raman spectra (FSRS) of [Ir2(2,5-dimethyl-2,5-diisocyanohexane)4]2+ (Ir(TMB)) in the region of low-frequency vibrations. Interpretation was supported by impulsive stimulated Raman experiments and time-dependent density-functional theory (TDDFT) calculations. The Ir-Ir stretching frequency doubled on going from ground to the lowest singlet excited state 1dσ*pσ, from 53 to 126 cm-1, demonstrating Ir-Ir bond formation. Spectral evolution during the first 4 ps after excitation showed extremely large-amplitude coherent oscillations of stimulated emission as well as FSRS signal intensities, which occurred with the excited-state Ir-Ir stretching frequency combined with frequencies of several deformation vibrations and the first Ir-Ir overtone. Corresponding vibrations were observed in FSRS directly but most of them vanished in the first 3 ps, indicating that they belonged to transiently populated hot vibrational states. Fourier transforms of intensity oscillations plotted against FSRS frequencies produced two-dimensional (2D-FSRS) maps with diagonal and off-diagonal features due to Franck-Condon-excited and anharmonically coupled vibrations, some of which acquired Raman intensity through coupling with the Ir-Ir stretch. We concluded that optical excitation impulsively shortens the Ir-Ir distance and increases its stretching force constant, assisted by a simultaneously excited network of coupled deformation modes. The electronically/vibrationally excited system then relaxes through periodic strengthening and weakening of the Ir-Ir interaction and changing conformations of the TMB ligand framework, forming a metal-metal bonded 1dσ*pσ state after 4-5 ps.